Instrument For Emotional Intelligence Using Exploratory Factor Analysis: Evidence From The Telecommunication Operators Of Pakistan (International Journal of Environmental Sciences, 2024)
Purpose of the Study: This study focused on understanding how the employees of telecom operators are in Pakistan are experiencing and expressing the Emotional intelligence. The researcher has developed the structured tool and refined to see its influence and reflection of employees capabilities in the working environment context. The researcher has adapted the instrument from the study of Wong and Law Emotional Intelligence Scale (WLEIS), which emphasizes four essential aspects of EI which are self-emotional appraisal explains about that how an individual understand their own emotions and others areas like others emotional appraisals, use of emotions and regulations of emotions. This study was not only focused to explore how these four emotional abilities are manifested among people in real organizational settings but also to ensure that the tool used to measure them is clear, consistent, and trustworthy. The process involved an in-depth statistical approach known as Exploratory Factor Analysis (EFA), which helped uncover the underlying emotional patterns and ensured that each dimension of EI is capturing within the unique cultural and organizational environment of Pakistan's telecom industry.Methodology: A structured survey was developed using a 10-point Likert interval scale, ranging from 1 (strongly disagree) to 10 (strongly agree), to measure Emotional Intelligence construct. The instrument comprised 16 items—four items per dimension—based on the WLEIS framework. The study adopted Exploratory Factor Analysis (EFA) using Principal Component Extraction and Varimax Rotation with the help of AMOS 24.0 to confirm the dimensional structure of the instrument. Before applying the extraction of components, the Kaiser-Meyer-Olkin (KMO) test conducted to measure sample adequacy and Bartlett’s Test of Sphericity applied to test for the suitability of factor analysis. The internal consistency and reliability of each dimension assessed using Cronbach’s Alpha.Main Findings: The Bartlett’s Test of Sphericity was statistically significant (p < 0.001), confirming that the correlation matrix was appropriate for factor analysis. The KMO value observed at 0.778, which is an excellent value as suggested by different studies. The EFA extracted four distinct components that aligned with the original structure of the WLEIS. These included Self-Emotion Appraisal (SEA), Others’ Emotion Appraisal (OEA), Use of Emotion (UOE), and Regulation of Emotion (ROE), with each of these components exhibiting Cronbach’s Alpha values above 0.8, ensuring internal consistency. The overall Cronbach’s Alpha for the 16-item scale was 0.808, indicating high reliability. These results validate the structure and psychometric properties of the Emotional Intelligence instrument in the context of Pakistan’s telecom industry.Applications of the Study: This instrument was tested and validated among employees—both male and female—working in telecom operators of Pakistan, such as Jazz, Telenor, Zong, PTCL, and Ufone and SCOM. The respondents included professionals from customer service, sales, technical Engineering teams, and administration departments. The validated instrument can be widely used for HR practices such as recruitment, leadership development, day-to-day operational interactions and employee appraisals. It can also support organizational interventions to enhance team performance, customer satisfaction, resilience, as well as academic research focused on EI, leadership behavior, and employee outcomes in developing economies. The study can add value for the routine trainings of HR about the role of emotional intelligence and its impact on employee performance and resilience.Novelty/Originality of the Study: This research contributes a significant value to both theory and practice. While several global studies have validated the WLEIS framework, few have examined its relevance in a South Asian, service-intensive, and culturally collectivist context like Pakistan’s telecom sector. The EFA results confirms the cross-cultural validity and dimensional clarity of EI when measured through this 16-item tool. The study recommends the necessity of developing context-specific instruments for better alignment with industry dynamics and employee characteristics in emerging markets.